EFEKTIVITAS MULTIVITAMIN DAN MENIRAN (Phyllanthus neruri L.) DALAM MENURUNKAN STRES PADA DOMBA SELAMA TRANSPORTASI - Satyaningtijas, Aryani S; Andriyanto, Andriyanto; Ramadhoni, Armando; Suci, Yulia; Dewi, Fitriana; Sutisna, Abadi (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Sheep is one of achievable animal protein sources. Therefore, they need to be transported to/in different places to fulfill the demand of mutton. This research was conducted to know the impact of transportation on stress as presented by leucocyte differentiation (N:L ratio). Blood were taken from sheep without stress transportation as a control for 12 hours.In this research, 12 sheep were divided into 3 groups: KP (control with stress),PA (stress with combination multivitamin and meniran - Phyllanthus niruri L.), PB (stress with combination multivitamin).Blood samples were taken at 0 hour (pre-transportation), 4h, 8h, 12h (during transportation) and 24h, 48h, 72h (post-transportation) to observe leucocyte differentiation. The results showed that ratio N:L (as stress indicator) were higher at all time periods during transportation and after the transportation. Sheep as a control group had reached the peak of ratio N:L at 0 h, meanwhile sheep with combination of multivitamin and meniran at 12 h and sheep with multivitamin only at 8. It means that the sheep with combination of multivitamin and meniran treatment was more effective to response the transportation stress.